Development of Coordination Abilities in Girls of Senior School Age through Artistic Gymnastics - Ю. В. Голенкова; А. В. Галкіна (OVS LLC, 2015)
The purpose of the research is to theoretically ground and experimentally verify the effectiveness of the effect of artistic gymnastics exercises on the development of coordination abilities of female high-schoolers. To achieve the tasks set, the research used the following methods: study and analysis of pedagogical, scientific and methodological literature, interviews with experts, pedagogical observations, pedagogical testing, methods of mathematical statistics. Research results. The paper grounds and experimentally verifies the effectiveness of the effect of artistic gymnastics exercises on the development of coordination abilities in female high-schoolers. It proves that the use of exercises borrowed from artistic gymnastics in physical training classes of high school (particularly: with no object (specific movements, balance, turns and jumps) and with objects (skipping rope, hoop, ball)) and of auxiliary exercises (classical choreography, ballroom and folk dances, musical-rhythmic and acrobatic exercises) helps improve the ability to feel the rhythm, movement coordination, the ability to maintain balance and spacial awareness.